2016
DOI: 10.1016/j.expneurol.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced vesicular monoamine transport disrupts serotonin signaling but does not cause serotonergic degeneration

Abstract: We previously demonstrated that mice with reduced expression of the vesicular monoamine transporter 2 (VMAT2 LO) undergo age-related degeneration of the catecholamine-producing neurons of the substantia nigra pars compacta and locus ceruleus and exhibit motor disturbances and depressive-like behavior. In this work, we investigated the effects of reduced vesicular transport on the function and viability of serotonin neurons in these mice. Adult (4–6 months of age), VMAT2 LO mice exhibit dramatically reduced (90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Our laboratory and others have previously demonstrated that VMAT2‐LO mice show decreased extracellular dopamine and norepinephrine concentrations compared with those measured in wild‐type mice . VMAT2‐LO mice also display decreased serotonergic transmission . Conversely, VMAT2‐HI mice show an increased capacity to store and release monoamines, particularly dopamine .…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our laboratory and others have previously demonstrated that VMAT2‐LO mice show decreased extracellular dopamine and norepinephrine concentrations compared with those measured in wild‐type mice . VMAT2‐LO mice also display decreased serotonergic transmission . Conversely, VMAT2‐HI mice show an increased capacity to store and release monoamines, particularly dopamine .…”
Section: Introductionmentioning
confidence: 69%
“…Primary outcome measure was peak dopamine release, which was evaluating by calculating the maximum current and dividing it by the calibration constant for that electrode. Measuring peak dopamine release is a common practice to determine stimulated neurotransmitter release . ANOVA with post hoc Dunnett's tests were performed to determine differences in peak stimulated dopamine release between genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, VMAT2 gene-dose has been linked to either neurotoxic or neuroprotective effects within each of the monoamine neurotransmitter systems including serotoninergic signaling (Alter et al, 2016), noradrenergic degeneration (Taylor et al, 2014), non-motor symptoms of PD (Taylor et al, 2009), and dopamine handling, toxicity, and dopamine-related neurodegeneration (Little et al, 2003; Lohr et al, 2015; Pifl et al, 2014). The significant expression of VMAT2 in dopaminergic regions such as the striatum and midbrain suggests possible sites of action for the previously reported VMAT2-mediated neuroprotection from toxic exposure to pesticides (Richardson et al, 2006), methamphetamine (Guillot et al, 2008; Lohr et al, 2015; Takahashi et al, 1997), and MPTP (Liu et al, 1992; Lohr et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, VMAT2-LO mice show neurodegeneration of the locus coeruleus (Taylor et al, 2014), a region that also degenerates in PD and shows immunoreactivity to our VMAT2 antibody. This observed reduction in immunoreactivity for VMAT2 in the VMAT2-LO mice is responsible for the disrupted serotonin signaling in these animals (Alter et al, 2016). These effects provide evidence that VMAT2 is broadly important in monoaminergic transmission, with higher gene-dose consistently linked to neuroprotection and lower gene-dose consistently linked to neurodegeneration and neuronal vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…In VMAT2 LO mice norepinephrine concentrations are also drastically reduced, illustrated by progressive degeneration in the locus coeruleus, that even preceded degeneration in the substantia nigra pars compacta (Taylor et al, 2014). A recent study revealed that at the age of 4–6 months VMAT2 LO mice also exhibited dramatically reduced serotonin release capacity (Alter et al, 2015). Thus, reducing the VMAT2 LO model primary to a dopaminergic deficiency is oversimplifying, and the same criticism can be applied to the hypothesis of apathy being mainly caused by dopaminergic dysfunction.…”
Section: Discussionmentioning
confidence: 99%